Determinants of Employee Work Productivity in UMKM Malang - Setyawati, Amelia; Nyuherno Aris Wibowo; Rayyan Sugangga; Adelia Rahma; Farij Ibadil Maula (Brilliant International Journal Of Management And Tourism, 2023)
The domino effect of the post-pandemic period is that many MSME actors who were previously successful have collapsed and even closed, on the other hand from the 2019-2021 Covid-19 pandemic, new MSME actors have grown, even to the point where they immediately opened many branches everywhere. To make MSMEs survive and be able to survive, MSME actors and their employees must remain productive. Every MSME will experience high levels of productivity maintained by disciplined team members. The effect of work discipline is having a strong work ethic will be able to carry out their duties as effectively and efficiently as possible, so that the MSME business can achieve its productivity goals. In addition, the work environment is very important for the MSME business strategy because it functions as a location where employees carry out their daily work activities. In MSME work productivity, motivation is often described as supporting productivity. This study aims to complete the gaps in previous studies by conducting a comprehensive study of the factors that increase the work productivity of MSMEs in Malang Raya which are influenced by work ethic, work motivation, work discipline and work environment. Researchers are motivated to do this research because the work productivity of MSMEs will have a positive impact on the growth of MSMEs.